PERAN TEKNOLOGI DALAM DIGITAL LEARNING - Pritandhari, Meyta; Wibawa, Fajri Arif (Lentera: Jurnal Ilmiah Kependidikan, 2021)
The existence of new technology has changed various aspects of life. The life of a traditional society has changed into a modern society. Learning in the era of the industrial revolution is required to be able to adapt to a variety of existing technologies and applications. With the technology and various applications can facilitate learning activities. Various learning activities carried out online that use technology. Digital learning is increasingly developing along with technological developments. Learning with modern technology that provides a variety of learning applications with various learning methods. Digital learning can be developed for distance learning. Digital learning can also be integrated with classroom learning (blended learning). This research uses descriptive qualitative method. In collecting data using in-depth interview techniques, documentation and observation. Data analysis uses Interactive Model Analysis analysis techniques. The role of technology in digital learning is very important, where technology is a major part of digital learning. Technology is not just included in the learning process, but technology must be able to improve the quality of learning. In digital learning educators and students can adjust learning needs with a variety of technological sophistication in a variety of existing learning applications, so that the learning process is fun and facilitates understanding of the material. The learning process by utilizing technology must be supported by educators and students so that learning using technology can run optimally.